In-situ analysis of sprayed concrete in a sewage tunnel lining. - Gabriella de Andrade Coni; Antonio Domingues de Figueiredo; Renan Pícolo Salvador; Renata Monte (Case Studies in Construction Materials)
The in-service condition of a sprayed concrete lining in a sewage tunnel was investigated. Video inspection was conducted alongside chemical, mineralogical, microstructural, and physical-mechanical analysis of core extracted from the tunnel lining. Reduced-size specimens were used to verify the mechanical and physical properties of the material along the thickness of the lining. However, the test results exhibited a high degree of scatter. In contrast, the chemical, mineralogical, and microstructural characterization proved to be efficacious techniques for measuring the degraded depth. The sulfate-rich sewer environment resulted in the formation of ettringite clusters up to a depth of 8 mm, which were mainly located in the entrapped air voids within the sprayed concrete microstructure. The interface between the primary and secondary linings exhibited greater water absorption and a notable reduction in strength. These regions represent potential weak spots within the lining. This research demonstrates the challenges associated with evaluating the properties of the sprayed concrete lining throughout its thickness in the absence of comprehensive and reliable information concerning the construction period. Subsequent analyses are necessary to ascertain the rate of degradation over time.